2010
DOI: 10.1088/0741-3335/52/12/124038
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic simulations of turbulent transport: size scaling and chaotic behaviour

Abstract: Important steps towards the understanding of turbulent transport have been made with the development of the gyrokinetic framework for describing turbulence and with the emergence of numerical codes able to solve the set of gyrokinetic equations. This paper presents some of the main recent advances in gyrokinetic theory and computing of turbulence. Solving 5D gyrokinetic equations requires state-of-the-art high performance computing techniques involving massively parallel computers and parallel scalable algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…As a side effect, judgments on the validity of local simulations for specific devices can be drawn. Naturally, the details of such a study depend to some extent on the chosen radial profiles which has been shown elsewhere [46,15,47]. In the present case, peaked temperature and density gradient profiles are chosen of the form…”
Section: The Local Limitmentioning
confidence: 95%
“…As a side effect, judgments on the validity of local simulations for specific devices can be drawn. Naturally, the details of such a study depend to some extent on the chosen radial profiles which has been shown elsewhere [46,15,47]. In the present case, peaked temperature and density gradient profiles are chosen of the form…”
Section: The Local Limitmentioning
confidence: 95%
“…The general trend that turbulent transport decreases with growing ρ * is a well established observation. 14,[19][20][21][22] Due to the narrow profile shape (see above) the convergence to the local limit occurs at relatively small ρ * . At this point it is important to remember that the fluxes are measured in units which imply the gyro-Bohm scaling, i.e.…”
Section: B System Size Scalingmentioning
confidence: 99%
“…This is a difficult task as bursts are chaotic: the turbulence has a so-called intrinsic variability. This phenomenon has been studied in [26] and [38] for ORB5 simulations: identical simulations differing only by the initialization are performed, and are compared by applying a moving time-average of width ∆t w . A standard deviation over the ensemble of simulations of about 15% is found for ∆t w = 500a/c s .…”
Section: Nonlinear Verificationmentioning
confidence: 99%